Expanding the clinical spectrum of biallelic ZNF335 variants. Issue 2 (3rd May 2018) - Stouffs, K.; Stergachis, A.B.; Vanderhasselt, T.; Dica, A.; Janssens, S.; Vandervore, L.; Gheldof, A.; Bodamer, O.; Keymolen, K.; Seneca, S.; Liebaers, I.; Jayaraman, D.; et al.
Abstract : ZNF335 plays an essential role in neurogenesis and biallelic variants in ZNF335 have been identified as the cause of severe primary autosomal recessive microcephaly in 2 unrelated families. We describe, herein, 2 additional affected individuals with biallelic ZNF335 variants, 1 individual with a homozygous c.1399 T > C, p.(Cys467Arg) variant, and a second individual with compound heterozygous c.2171_2173delTCT, p.(Phe724del) and c.3998A > G, p.(Glu1333Gly) variants with the latter variant predicted to affect splicing. Whereas the first case presented with early death and a severe phenotype characterized by anterior agyria with prominent extra‐axial spaces, absent basal ganglia, and hypoplasia of the brainstem and cerebellum, the second case had a milder clinical presentation with hypomyelination and otherwise preserved brain structures on MRI. Our findings expand the clinical spectrum of ZNF335 ‐associated microcephaly. Abstract : Biallelic ZNF335 variants were identified in 2 affected individuals, 1 individual with a homozygous c.1399T>C, p.(Cys467Arg) variant, and a second individual with compound heterozygous c.2171_2173delTCT, p.(Phe724del) and c.3998A>G, p.(Glu1333Gly) variants; the latter variant is predicted to affect splicing. Whereas the first case presented with early death and a severe imaging phenotype characterized by anterior agyria with prominent extra‐axial spaces, absent basal ganglia, and hypoplasia of the brainstem and cerebellum, the second case had a milder clinical presentation with hypomyelination and otherwise preserved brain structures on MRI.